Cardiometabolic deaths in black and white men: Tracing the risks from early- to mid-adulthood - Rebecca Arden Harris; Sameed Ahmed M. Khatana; Judith A. Long (Preventive Medicine Reports)
Objective: This study aimed to estimate and compare cardiometabolic disease (CMD) mortality in U.S. Black and White men during the transition from early adulthood to middle age. Methods: Using 2022 National Vital Statistics System data and standard period life table methods, we estimated the risk of CMD death in hypothetical cohorts of Black and White men from age 25 to 45 years. We estimated cumulative risk, excess mortality, years of lost life (YLL), and proportion of deaths due to CMD, stratifying by metabolic and cardiovascular disease. Results: Of the 325,134 Black men aged 25 years in the initial cohort, the cumulative risk of cardiometabolic death before age 45 was one in 63 individuals or 1.58 %. For White men, the risks were markedly lower. Of the 1,185,384 White men aged 25 years in the initial cohort, the cumulative risk of cardiometabolic death before age 45 was one in 158 individuals or 0.63 %. The study also found that of the 5141 expected CMD deaths in the Black cohort, 3090 or 60.10 % were excess deaths relative to the White cohort. Additionally, the proportion of all deaths due to CMD among Black men was 19.15 % rising from 6.02 % at age 25 to 38.00 % at age 45, compared with 11.10 % among White men, increasing from 4.57 % at age 25 to 19.79 % at age 45. The YLL for Black men averaged 6.72 months per person while White men averaged 2.94 months. Conclusions: This investigation shows profound racial disparities in CMD mortality from early to mid-adulthood.